2022
DOI: 10.26907/2541-7746.2022.2-3.221-243
|View full text |Cite
|
Sign up to set email alerts
|

About the Causes of the Bearing Capacity Loss of a Composite Beam under Three-Point Bending

Abstract: This article considers the results of an experimental and numerical study of the threepoint bending problems of a composite specimen (beam). The numerical analysis of the beam behavior, in a physically and geometrically nonlinear statement of the problem, assumed that the beam is made by layering a unidirectional carbon fiber along the specimen axis. The Tsai-Wu criterion was used to determine the ultimate load at which the composite phases of the specimen lose their strength. The comparative analysis of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…ˆĜG  = dependence stated in [18,19] and based on formulas (1), ( 3), relations ( 6) and ( 11) has a sufficient degree of accuracy in the central zone of the specimen with [± 45°]2 lay-up at 2 s  .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ˆĜG  = dependence stated in [18,19] and based on formulas (1), ( 3), relations ( 6) and ( 11) has a sufficient degree of accuracy in the central zone of the specimen with [± 45°]2 lay-up at 2 s  .…”
Section: Discussionmentioning
confidence: 99%
“…we construct a shear strain curve ( ) It should be noted that in tensile tests of specimens with [0°]s and [90°]s lay-ups ( s is the number of lamina in the specimen) with fibers located along and across to the direction of the acting load the mechanical characteristics of a single monolayer of fiber reinforced composite in its orthotropy axis 12 , xx have been determined earlier. The corresponding stress-strain curve for a unidirectional CFRP can be considered linear up to the failure of the specimens [15,16]. This fact makes it possible to determine elastic moduli EE  =…”
Section: Relationships For Determining the Components Of Stresses And...mentioning
confidence: 99%
“…As is known [13,14], when compressing specimens from unidirectional FRP along the fibers, the values of the transverse shear modulus can be taken as the ultimate compressive stresses. In a series of works [15,16], it was shown that the theoretical identification of the shear buckling form of composite specimens under threepoint bending conditions is possible using equations based on the simple kinematic model of S. P. Timoshenko.…”
Section: Introductionmentioning
confidence: 99%